(3GdCUhd aj GdfMhs - (3CHhHcQ eMeO Hf GdSQj Hf Sgd GdeYQha HGHf GdSQGL,J (B316 (3g` s
(3ChdgG (B:s
(3bGd CHh HcQ eMeO Hf GdSQi GdfMhi GdfMh EfeG CQjO Hg Cf jfLh GdeJcde EPG JYdeg cdGe GdYQH s
(3BNQgG (B:s
(3BNQ eG LGA ajg (B: (3LGAfi YGbd , heQQJ HXQja , hdjS HGdMSf s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B136s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
Keywords: (3GdfMhs